2017
DOI: 10.1080/21541248.2017.1362495
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and functions of RhoU and RhoV

Abstract: Rho GTPases play central roles in a wide variety of cellular processes, including cytoskeletal dynamics, cell adhesion and cell polarity. RhoU and RhoV are Rho GTPases that have some atypical properties compared with classical Rho family members, such as the presence of N-and C-terminal extension regions, unusual GDP/GTP cycling and post-translational modification by palmitoylation but not prenylation. Their activity and localization is regulated by the N-terminal and C-terminal regions, and so far no GEFs or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…We thus began to consider whether post-translational modification of RhoU was impaired. RhoU is thought to be targeted to membranes by palmitoylation [16] and we confirmed that RhoU can be palmitoylated (Fig. 3b).…”
Section: Fasn Depletion Reduces Rhou Palmitoylationsupporting
confidence: 79%
“…We thus began to consider whether post-translational modification of RhoU was impaired. RhoU is thought to be targeted to membranes by palmitoylation [16] and we confirmed that RhoU can be palmitoylated (Fig. 3b).…”
Section: Fasn Depletion Reduces Rhou Palmitoylationsupporting
confidence: 79%
“…ZCL278 blocks the interaction of Cdc42 with intersectin (Friesland et al, 2013) and can inhibit the growth of lung cancer xenografts (Aguilar et al, 2019). It is important to note that the activity of atypical Rho GTPases is unlikely to be regulated by GEF/GAP interactions (Aspenstrom et al, 2007;Hodge and Ridley, 2017), and therefore alternative strategies will be required to target these family members effectively.…”
Section: Targeting Rho Gtpase Activationmentioning
confidence: 99%
“…The RhoU/RhoV and RhoD/RhoF subfamilies represent another type of atypical Rho GTPases. These family members have high intrinsic guanine nucleotide exchange activity, and are assumed to be mostly GTP-bound in cells [17,18]. Because these atypical Rho GTPases also have GTPase activity and can cycle between GDP-bound and GTP-bound forms, they are considered to be the fast-cycling Rho GTPases [6,19,20].…”
Section: Regulation Of Rho Gtpases By Ptmsmentioning
confidence: 99%